Technical and economic aspects of coke gasification in the petroleum refining industry - Sato, André Kiyoshi Coutinho [UNESP]; Paulino, Regina Franciélle Silva [UNESP]; de Campos, Victor Arruda Ferraz [UNESP]; Tuna, Celso Eduardo [UNESP]; Silveira, José Luz [UNESP] (Elsevier, 2022)
Petcoke has applications as an energy source in the industry, serving as fuel for power generation or through the Integrated Gasification Combined Cycle (IGCC) system for the production of syngas and electricity. This kind of technology prioritize the production of electric energy efficiently through a combined cycle integrated with a gasification system. The novelty of this work is the consideration of the use of petcoke for increasing electricity potential generation in the refinery regarding Brazilian conditions. In this paper, it is studied the application of the petcoke gasification in an actual refinery located in the Vale do Paraiba region, São José dos Campos city. In this analysis, thermodynamics studies are carried out on the potential for electricity production and the global efficiency of the process using IGCC technology in the Brazilian oil refinery. Also, economic analysis is applied for the determination of the electricity production cost, the annual saving expected and the payback period of the system. As conclusions, the studies showed a net efficiency in the electricity production of 41.2% with a production capacity of 260 MW. It was found that the specific investment cost of the system was US$ 2719.2/kW and the cost of energy production tends to stabilize at US$ 0.083/kW, and the payback is between 7 and 10 years when the cost of electricity is considered as US$ 0.109/kWh.
Keywords: Integrated gasification combined cycle; Petcoke; Syngas